Understanding human communication. - Adler, Ronald; Rodman, George (Orlando: Harcourt brace collegge publishers, 1997)
Contents: 1. elements of communication: what and why, 2. interpersonal communication, understanding interpersonal relationship, 3. communication in groups, the nature of groups, 4. public communication, choosing and developing a topic, persuasive speaking, presenting your message, informative speaking.
Glosary p. 503-511 Index p. 519
Keywords: Comunicación Social